2020
DOI: 10.1002/adtp.202000072
|View full text |Cite
|
Sign up to set email alerts
|

Effective Delivery of the CRISPR/Cas9 System Enabled by Functionalized Mesoporous Silica Nanoparticles for GFP‐Tagged Paxillin Knock‐In

Abstract: In this study, direct and effective intracellular delivery of CRISPR/Cas9 plasmids for homology‐directed repair is achieved by functionalized mesoporous silica nanoparticles (MSNs). The functionalized MSNs (Cy5.5‐MSNs‐NLS) are synthesized by in situ labeling of a fluorescent dye (Cy5.5) and surface conjugation of nuclear localization sequence (NLS, PKKKRKV), showing a high loading efficiency (50%) toward the plasmids (PXN cutdown plasmid: GFP‐Cas9‐paxillin_gRNA and repair plasmid: AICSDP‐1: PXN‐EGFP). Subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 43 publications
0
25
0
Order By: Relevance
“…Xu et al constructed poly(dimethyldiallylammonium chloride) (PDDA)-coated and NLS-modified mesoporous silica nanoparticles (MSNs) for the co-delivery of Cas9 plasmids together with an EGFP DNA template for HDR. 168 The results indicated that the GFP-tag was successfully inserted at the desired locus. Likewise, Zhang et al constructed PAMAM and aptamer coated MSNs for the co-delivery of a Cas9 plasmid and sorafenib.…”
Section: Biomaterials Science Reviewmentioning
confidence: 98%
“…Xu et al constructed poly(dimethyldiallylammonium chloride) (PDDA)-coated and NLS-modified mesoporous silica nanoparticles (MSNs) for the co-delivery of Cas9 plasmids together with an EGFP DNA template for HDR. 168 The results indicated that the GFP-tag was successfully inserted at the desired locus. Likewise, Zhang et al constructed PAMAM and aptamer coated MSNs for the co-delivery of a Cas9 plasmid and sorafenib.…”
Section: Biomaterials Science Reviewmentioning
confidence: 98%
“…For Example, Ehgartner et al introduced sensor spots integrated with silicon-glass microreactors connected with commercial optical readout devices [ 78 , 79 ]. Figure 3 A represents the chip and its sensing spots (left) as well as the commercial picolo2 readout with a USB port (right) which can be connected to the computer for further analysis.…”
Section: Oxygen Sensors In On-chip Systemsmentioning
confidence: 99%
“…In another development, Wang and colleagues developed a portable detector for O 2 detection using a PDMS chip and a PtTFPP film [ 79 , 80 ]. The detector ( Figure 3 C), comprised of a photomultiplier (PMT) counter (with a Charge Coupled Device (CCD) camera and an imaging spectrograph) connected to a smart-phone application and was able to detect DO levels with an LOD of 0.01 mg/L (0.37 µM) and short response time of 22 s. The simplicity, low-cost production, handling of the device, high sensitivity, short response time and portability are among important features which make this detector a desirable device for on-chip O 2 sensing, especially in medical applications.…”
Section: Oxygen Sensors In On-chip Systemsmentioning
confidence: 99%
“…Due to various features including size, morphology, availability of the functionalized groups, surface charge, and higher delivery efficiency compared to the other analogues, there is a growing interest in nanoporous materials in developing nanocarriers for delivery of biological molecules [ 36 42 ]. Recently, mesoporous silica nanoparticles (MSN) have been recognized as promising nanocarriers for drug and gene delivery due to their unique ordered porous nanostructured, large pore volume, good stability, high surface area, acceptable biocompatibility, ease of surface functionalization, and loading/release efficacy [ 43 45 ]. MSNs-based nanostructures offer unique features for attaining appropriate nanocarriers for various exploitation that cannot be easily met by the other nanostructures [ 46 48 ].…”
Section: Introductionmentioning
confidence: 99%